The Relationship between Legal Effectiveness Theory and Coaching Effectiveness Prisoners in Correctional Institutions - Mulyadi Mulyadi (Focus Journal : Law Review, 2024)
This research discusses the relationship between legal effectiveness theory and the effectiveness of coaching prisoners in correctional institutions. That the effectiveness of the law for training prisoners in order to achieve the objectives of punishment in correctional institutions. In this research the author uses a normative research method, namely a method that discusses research analysis using books, laws and concepts and theories. The research results show that the theory of legal effectiveness is closely related to the effectiveness of the implementation of laws relating to the development of prisoners in correctional institutions. These prisoners also really need good guidance and direction from correctional officers who play an important role in providing guidance and direction to prisoners during their detention period. Legal effectiveness, in this case, effectiveness is related to the rehabilitation of prisoners based on the implementation of legal validity. Legal validity refers to a legal norm that has binding force, requiring society to obey and act in accordance with the provisions of legal norms. To ensure that people are willing to obey the law, one of the efforts made is to establish sanctions, especially negative sanctions. The aim of applying sanctions among the public is to prevent them from committing disgraceful acts, thereby achieving the desired legal effectiveness and realizing the intended goals.